Second European quality of life survey family life and work - Kotowska, Irena E.; Matysiak, Anna.; Styrc, Marta; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
Demographic change and labour market developments are shaping the work and family life of Europeans, with far-reaching consequences for the future. Demographic change has been triggered by changing patterns of family formation, and shifts in the roles of men and women in the home, along with increased life expectancy and geographic mobility. Transformations in the labour market have resulted in increasing economic instability and job uncertainty, together with a rise in labour productivity and flexibility. The second European Quality of Life Survey (EQLS), carried out by the European Foundation for the Improvement of Living and Working Conditions (Eurofound) in 2007, offers a wide-ranging view of the diverse social realities in the 27 EU Member States, Norway and the candidate countries of Croatia, the former Yugoslav Republic of Macedonia and Turkey.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books